Quadrature Phase Shift Keying Modulation and Demodulation Simulation Using MATLAB - Yao Xuan, Chung; Joret, Ariffuddin (Evolution in Electrical and Electronic Engineering, 2022)
People across the world utilize the 4G wireless communication system. A wireless communication system is one where data is transmitted wirelessly from one point to another without using an electrical conductor as a medium. Quadrature Phase Shift Keying (QPSK) is a technique used for modulation in wireless communication systems. Signal noise is unwanted noise that degrades the performance of wireless communication infrastructure. Many individuals have expressed concern about how signal power would affect QPSK modulation and demodulation. This project simulates QPSK modulation and demodulation. The problem is determining if the noise affects the output data of QPSK modulation and demodulation by modifying the power value of the noise at each time point of the simulation. The graph and data show how noise will affect the output data of QPSK modulation and demodulation. The bit error rate of the data increases with the strength of the noise. The probability of receiving data also increases with the noise power.